Social Performance Incentives in Mission-Driven Firms - Jung, Sun-Moon; Shin, Jae Yong (Management Science, 2022)
We examine the effect of introducing an incentive plan based on social performance in a sample of 186 social mission–oriented firms in Korea. We find that the social performance of social enterprises (SEs) significantly improves over time after adoption of an incentive plan based on social performance, and that the incentive effect increases with managers’ perceived measurability of social performance. Moreover, we document that social bonuses do not harm SEs’ financial performance and that they have a positive spillover effect on financial performance in SEs that have a higher level of task complementarity between social and financial goals. Our results also show that when the main beneficiary of social bonuses is expected to be a firm’s employees, the incentive effect of social bonuses decreases (increases) with a firm’s focus on social controls (formal controls). In contrast, when the main beneficiary is expected to be a firm’s social mission, the incentive effect increases with a firm’s reliance on social controls. This paper was accepted by Suraj Srinivasan, accounting.